An Analysis of Instagram Live Performance for Health Promotion Strategy: a Case Study of @iakmitangsel - Maruf, Mohammad Ainul; Utomo, Muhammad Wiji; Nurfizri, Syifa; Ardila, Septiyani (J-Mestahat, 2023)
There is a growing interest in leveraging social media platforms for health education and health promotion. This study focuses specifically on Instagram Live, a feature that allows real-time video streaming, to assess its effectiveness in disseminating health-related information and engaging the audience. This research employs a quantitative analysis of engagement metrics of @iakmitangsel’s Instagram Live performance from March to June 2023. The results revealed that Content J had the highest number of views (323) and likes (53). Content I had the lowest number of views (132), while Content B and H had the lowest number of likes (13 each). Content G had the highest number of accounts reached by followers (224), content J had the highest number of accounts reached by non-followers (241), while Content D received the highest number of impressions (561). On the other hand, Content H had the lowest number of accounts reached by follower (118) and Content B had the lowest number of accounts reached by non-follower (27) and the lowest number of impressions (239). The findings of this research will contribute to the knowledge base surrounding the use of Instagram Live as a health promotion strategy, specifically within the context of South Tangerang City. Keywords: social media, engagement metric, health promotion